Blood pressure‐independent inhibition of Marfan aortic root widening by the angiotensin II receptor blocker valsartan. Issue 10 (27th May 2021) - Tehrani, Arash Y.; White, Zoe; Milad, Nadia; Esfandiarei, Mitra; Seidman, Michael A.; Bernatchez, Pascal
Abstract: Marfan syndrome (MFS) is a genetic disorder that results in accelerated aortic root widening and aneurysm. However, management of MFS patients with blood pressure (BP)‐lowering medications, such as angiotensin II (AngII) receptor blocker (ARB) losartan, continues to pose challenges due to their questionable efficacy at attenuating the rate of aortic root widening in patients. Herein we investigate the anti‐aortic root widening effects of a sub‐BP‐lowering dose valsartan, an ARB previously linked to non‐BP lowering anti‐remodeling effects. Despite absence of BP‐lowering effects, valsartan attenuated MFS aortic root widening by 75.9%, which was similar to a hypotensive dose of losartan (79.4%) when assessed by ultrasound echocardiography. Medial thickening, elastic fiber fragmentation, and phospho‐ERK signaling were also inhibited to a similar degree with both treatments. Valsartan and losartan decreased vascular contractility ex vivo between 60% and 80%, in a nitric oxide (NO)‐sensitive fashion. Valsartan increased acetylcholine (Ach)‐induced vessel relaxation and phospho‐eNOS levels in the aortic vessel supporting BP‐independent activation of protective endothelial function, which is critical to ARB‐mediated aortic root stability. This study supports the concept of achieving aortic root stability with valsartan in absence of BP‐lowering effects, which may help address efficacy and compliance issues with losartan‐based MFS patient management. Abstract : Inhibition of Marfan aortic root remodeling and widening with blood pressure lowering medications losartan and valsartan. However, valsartan was used at sub‐blood pressure lowering dose, therefore implying blood pressure independence.